1994
DOI: 10.1071/pp9940791
|View full text |Cite
|
Sign up to set email alerts
|

Starch Synthesis in the Kernel of Wheat Under High Temperature Conditions

Abstract: As temperature rises above 18-22�C, the observed decrease in the duration of deposition of dry matter in the kernel is not accompanied by a compensating increase in the rate of grain filling with the result that grain weight (and yield) is diminished at high temperature. Reduced starch content accounts for most of the reduction in grain dry matter at high temperature. Responses to temperature in the low temperature range, 20-30�C (the LTR), could possibly be ascribed to the temperature response characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
112
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(128 citation statements)
references
References 33 publications
13
112
1
2
Order By: Relevance
“…Yet, at a cellular level, although about 80% of cellular enlargement occurs between the end of cellular division and the conclusion of dry matter accumulation (Nicolas et al, 1984), the rate of cellular volumetric augmentation does not compensate the decreasing extent of cellular enlargement (Stone et al, 1995. Caley et al (1990 and Jenner (1994) further confirmed these data, and Shpiler and Blum (1986), working with field trials, also reported that grain maturity develops earlier, producing smaller and shriveled grains, in heat stressed genotypes.…”
Section: Introductionsupporting
confidence: 67%
“…Yet, at a cellular level, although about 80% of cellular enlargement occurs between the end of cellular division and the conclusion of dry matter accumulation (Nicolas et al, 1984), the rate of cellular volumetric augmentation does not compensate the decreasing extent of cellular enlargement (Stone et al, 1995. Caley et al (1990 and Jenner (1994) further confirmed these data, and Shpiler and Blum (1986), working with field trials, also reported that grain maturity develops earlier, producing smaller and shriveled grains, in heat stressed genotypes.…”
Section: Introductionsupporting
confidence: 67%
“…These findings challenge the notion that the rapid reduction in photosynthetic capacity during the heat treatment in the susceptible genotypes (Drysdale, Frame, Lyallpur-73 and Reeves) directly reduced their grain weights (by limiting source supply), as the responses of their developing grains to heat were characterised by a reduction in GFD rather than a reduction in grain filling rate. Similarly, the consistent trend for heat to increase grain filling rate during the treatment, and the absence of a significant reduction in MGR following heat treatment (except in Waagan) argues against damage to the grain soluble starch synthase as being very influential under these conditions, despite other evidence that this enzyme is heat-sensitive (Jenner 1994). An alternative explanation for why grain filling was cut short in these varieties is that heat accelerated senescence in the grain, curtailing the development of the grains and their ability to convert the delivered sugars into starch.…”
Section: Grain Growth and Developmentmentioning
confidence: 99%
“…Soluble starch synthase has been identified as both the ratelimiting and most heat-sensitive component of the starch biosynthetic machinery of the developing wheat grain, although the effect of heat on soluble starch synthase appears to be reversible (Jenner 1994). Elevated temperatures raise respiration rates in the grains and spike, thereby limiting the sugar pools available for starch deposition (Wardlaw et al 1980).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The yield losses are caused by a reduction in the starch content, since over 65% of cereal kernels is composed of starch (Jenner 1994;Barnabás et al 2008). Starch accumulation is correlated with the sucrose content of the kernels and with the activity of sucrose synthase and other enzymes with an important role in starch synthesis .…”
mentioning
confidence: 99%